Kontribusi Dakwah William Henry Quilliam dalam Membentuk Transformasi Identitas Muslim di Inggris - Arifah, Afro' Anzali Nurizzati; Ichwayudi , Budi; Maulidatus Syahrotin Naqqiyah (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
William Henry Quilliam was a convert who dedicated himself to preaching to spread Islam in England, especially in the Liverpool area. Quilliam's da'wah was fully supported by the Muslim community occupying Britain but only as an immigrant because of its open nature and willingness to listen to criticism. The success of Quilliam's da'wah was even more evident when his da'wah was able to attract the attention of non-Muslims to convert. Quilliam's traditionalist thinking is able to provide good intake to the extremist souls that often appear in British society. This research aims to see how Quilliam's da'wah can shape a change in Muslim identity in Britain as well as the response of the British people to the existence of Quilliam as a convert who is able to preach Islam in Britain. The research method used in this study is qualitative with the type of library research. In addition, this study uses the theory of da'wah agenda setting Maxwell McComb and Donald L. Shaw to explain that the media in da'wah has an influence in shaping public opinion. The results of this study provide evidence that the success of the Quilliam da'wah process is seen from the change in Muslim identity in Britain and the extent of the response of the British people to the existence of Quilliam.